2013
DOI: 10.5380/ce.v18i2.32583
|View full text |Cite
|
Sign up to set email alerts
|

Internação Em Uma Unidade De Emergência Hospitalar: Vivência

Abstract: Objetivou-se descrever a vivência de familiares de pacientes atendidos em uma Unidade de Emergência de Fortaleza-Ceará acerca de sua colaboração nas atividades e dificuldades vivenciadas. Estudo descritivo, com abordagem qualitativa, foi desenvolvido com 34 familiares acompanhantes de pacientes que se encontravam em observação. Os dados foram coletados por meio de entrevistas com roteiro semiestruturado no período de outubro e novembro de 2010 e a análise foi feita de acordo com a temática de conteúdo. Os resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
8

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
0
7
0
8
Order By: Relevance
“…This fact, added to other aspects, will provide a more helpful, safe, holistic care, focused on the aspirations of the other, not only from the patients to their families, thus reducing the suffering. From an analogy, the study performed with relatives of patients assisted in an emergency unit in the South of Brazil identified that they presented feelings of gratitude towards the health professionals, and the fulfillment of their role as family members in regards to the possibility to observe the improvement of the health condition of their beloved ones, and to have helped in the relief in the suffering and in care, specially the emotional one, to their ill relative (2) . When considering the real possibility to insert the families in the emergency room, it is necessary to call attention to the way each person reacts in different manners when experiencing emergency care of a relative.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This fact, added to other aspects, will provide a more helpful, safe, holistic care, focused on the aspirations of the other, not only from the patients to their families, thus reducing the suffering. From an analogy, the study performed with relatives of patients assisted in an emergency unit in the South of Brazil identified that they presented feelings of gratitude towards the health professionals, and the fulfillment of their role as family members in regards to the possibility to observe the improvement of the health condition of their beloved ones, and to have helped in the relief in the suffering and in care, specially the emotional one, to their ill relative (2) . When considering the real possibility to insert the families in the emergency room, it is necessary to call attention to the way each person reacts in different manners when experiencing emergency care of a relative.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, health professionals must inform about the illness, the signs and symptoms, the diagnose, the treatment, and the follow up to other health units. The previous knowledge can facilitate the process of acceptance of the illness, enabling the family to get organized again to overcome the stressing situation and to think in the rehabilitation of their beloved one (2) . Besides that, it is important to take into consideration the indication from the relatives in which, by enabling the presence of the families in the emergency rooms, it will increase the chance they early and easily understand the medical condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alguns preferem que os familiares não permaneçam durante o atendimento de emergência, pois acreditam que isto pode influenciar negativamente no desempenho da equipe, enquanto outros enfatizam a importância da presença da família durante situações de emergência, pelo suporte emocional que oferecem, sendo fundamental para a recuperação da criança (5)(6)(7)(8) . Para a equipe de saúde, compreender a humanização em ambientes de cuidados complexos significa acolher a dinamicidade da organização que promove as relações/interações humanas e profissionais.…”
Section: Introductionunclassified